Dinamika Oseanografi Air Laut (Kimia dan Fisika) Sekitaran Kawasan Mangrove Teluk Kendari Sulawesi Tenggara - Anwar Said; Suharta Amijaya Husen (LP3M Universitas Muhammadiyah Kendari, 2021)
Kendari bay covers an area of roughly 19.05 Km2 that boasts the mangrove ecosystem, where development around the gulf of Kendari resulted in changes in environmental conditions especially in the water quality that affected the mangrove ecosystem around the bay. The aim of this study was to analyze the oceanographic dynamics of the waters in the gulf of Kendari. The direct results include degrees of acidity (pH), temperatures, salinity and tides at 3 point measurements stations in the waters surrounding the Kendari bay mangrove ecosystem. The result is that the gulf of Kendari has a degree of acidity (pH) 6-7, the average temperature of 27°C - 29°C, a salinity of the 30-30 ppt interval, which in turn the tide of the gulf of Kendari is that the first high tide of 177 cm occurs at 2 p.m. and the second high tide of 190 cm occurs at 2 a.m. Whereas the first low tide of 74 cm occurs at 8 p.m. and the second low tide of 9 cm occurs at 8 a.m.